Leads and hurdles to sustainable microbial bioplastic production. (October 2022) - Varghese, Sherin; Dhanraj, N.D.; Rebello, Sharrel; Sindhu, Raveendran; Binod, Parameswaran; Pandey, Ashok; Jisha, M.S.; Awasthi, Mukesh Kumar
Abstract: Indiscriminate usage, disposal and recalcitrance of petroleum-based plastics have led to its accumulation leaving a negative impact on the environment. Bioplastics, particularly microbial bioplastics serve as an ecologically sustainable solution to nullify the negative impacts of plastics. Microbial production of biopolymers like Polyhydroxyalkanoates, Polyhydroxybutyrates and Polylactic acid using renewable feedstocks as well as industrial wastes have gained momentum in the recent years. The current study outlays types of bioplastics, their microbial sources and applications in various fields. Scientific evidence on bioplastics has suggested a unique range of applications such as industrial, agricultural and medical applications. Though diverse microorganisms such as Alcaligenes latus, Burkholderia sacchari, Micrococcus species, Lactobacillus pentosus, Bacillus sp ., Pseudomonas sp., Klebsiella sp., Rhizobium sp., Enterobacter sp., Escherichia sp., Azototobacter sp., Protomonas sp., Cupriavidus sp., Halomonas sp., Saccharomyces sp., Kluyveromyces sp., and Ralstonia sp. are known to produce bioplastics, the industrial production of bioplastics is still challenging. Thus this paper also provides deep insights on the advancements made to maximise production of bioplastics using different approaches such as metabolic engineering, rDNA technologies and multitude of cultivation strategies. Finally, the constraints to microbial bioplastic production and the future directions of research are briefed. Hence the present review emphasizes on the importance of using bioplastics as a sustainable alternative to petroleum based plastic products to diminish environmental pollution. Graphical abstract: Image 1 Highlights: Overview of microbial bioplastics. Leads and hurdles of microbial bioplastics were discussed. Diverse applications were discussed.